Occurrence, properties and pollution potential of environmental minerals in acid mine drainage - Valente, Teresa Maria Fernandes (2009)
This paper describes the occurrences, the mineralogical assemblages and the environmental relevance of the AMD-precipitates from the abandoned mine of Valdarcas, Northern Portugal. At this mining site, these precipitates are particularly related with the chemical speciation of iron, which is in according to the abundance of mine wastes enriched in pyrrhotite and pyrite. The more relevant supergene mineralogical assemblages include the following environmental minerals: soluble metal-salts, mainly sulphates, revealing seasonal behaviour, iron-hydroxysulphates and iron-oxyhydroxides, both forming ochre precipitates of poorly and well-crystalline minerals. Pollution potential of the most highly water soluble salts was analysed in order to evaluate the environmental effect of their dissolution by rainfall. Laboratory experiments, carried out with iron and aluminium sulphates, demonstrated the facility to release metals, sulphate and acidity upon dissolution. Regarding the ochre precipitates, composed by several less soluble iron (III)-minerals, the spatial distribution on the nearby aqueous system as well as the proportion of Jarosite, Schwertmannite and Goethite in the mixtures gave information about the halo’s contamination promoted by the AMD emerging from the waste-dumps